2018
DOI: 10.1007/s00784-018-2558-z
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of vertical root fracture in teeth close and distant to implant: an in vitro study to assess the influence of artifacts produced in cone beam computed tomography

Abstract: Since nowadays, many patients who undergo CBCT show implants and they definitively produce artifacts, it is important to evaluate the influence of such artifacts in the diagnosis of teeth that are close to the generator-artifact object.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 36 publications
3
46
1
1
Order By: Relevance
“…, Freitas et al . ). On the other hand, in clinical situations, one assesses not only the presence of the fracture itself but also the shape, localization, and size of bone resorption adjacent to the fracture; that is, the fracture may not be detected, but can be diagnosed (Fayad et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…, Freitas et al . ). On the other hand, in clinical situations, one assesses not only the presence of the fracture itself but also the shape, localization, and size of bone resorption adjacent to the fracture; that is, the fracture may not be detected, but can be diagnosed (Fayad et al .…”
Section: Introductionmentioning
confidence: 97%
“…The presence of multiple metal constructions in teeth with VRF as well as in adjacent teeth (e.g. posts, post-cores, crowns, implants) may also decrease the efficacy of CBCT for the detection of a fracture because of artefacts causing significant image degradation and misrepresentation in the region of interest (Tadinada et al 2015, Freitas et al 2018). On the other hand, in clinical situations, one assesses not only the presence of the fracture itself but also the shape, localization, and size of bone resorption adjacent to the fracture; that is, the fracture may not be detected, but can be diagnosed (Fayad et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Such materials include dental restorations and metal crowns, dental implants, gutta-percha, and metal posts. Restorations and crowns create artifacts at the level of dental crowns, which may affect the diagnosis of carious lesions, 4 while the other materials generate artifacts at the level of dental roots and alveolar bone, negatively influencing the ability of clinicians to detect conditions such as root fractures, 5,6 root resorptions, 7 and bone defects. 8 The production of artifacts in regions adjacent to highdensity materials is relatively well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Another study recommended removing root canal filling material before taking images to increase the potential of CBCT [36]. Using the metal artifact reduction (MAR) algorithm improves the specificity; its use is recommended when there are metal objects near teeth with suspected VRF [37]. Other authors have reported protocols with smaller FOVs and voxels and achieved better sensitivities and specificities when detecting horizontal root fracture [38,39].…”
Section: Discussionmentioning
confidence: 99%